Treatment of high-ammonia-nitrogen landfill leachate nanofiltration concentrate using an Fe-loaded Ni-foam-based electro-Fenton cathode. Issue 5 (October 2020) - Wang, Yanqiu; Meng, Guangcai; Shan, Mingjun; Wang, Dongyang; Bai, Zhongteng; Zhou, Xinyu; Lv, Yanli; Bai, Jinfeng
Graphical abstract: Highlights: An electro-Fenton process without Fe-sludge or an external catalyst was employed. An Fe-loaded electro-Fenton cathode was used to treat landfill leachate concentrate. COD, NH3 -N, and color were simultaneously eliminated. High NH3 -N LLC from failed seasonal nitrification were treated. Abstract: In order to treat high-ammonia-nitrogen (NH3 -N) landfill leachate nanofiltration concentrate (LLNC), an Fe-loaded, activated C-based Ni-foam composite electrode was prepared via ferrous ion impregnation and calcination in a nitrogen atmosphere. The composite electrode was used as a cathode and combined with a dimensionally stable anode (DSA) to form the electro-Fenton system. On the basis of single-factor experiments, a response surface methodology (RSM) was applied to evaluate the influence factors. A second-order polynomial was then obtained, and the optimum treatment conditions for the LLNC were found to include an applied voltage of 10 V, initial pH of 2.81, electrode spacing of 1.53 cm, chemical oxygen demand (COD) removal rate of 77.24 % at 300 min, and an applied voltage of 9.02 V, initial pH of 3.90, electrode spacing of 1.04 cm, and an NH3 -N removal rate of 74.62 %. Three-dimensional excitation-emission matrix fluorescence spectroscopy of the LLNC before and after the electro-Fenton reaction revealed that the fluvic and humic acid-like substances, as well as the soluble microbial byproducts, were effectively removed from the LLNC. These results indicate that the electro-Fenton system can both inhibit the consumption of Fe ions and efficiently reduce the pollution indices (e.g., COD, NH3 -N, and color) of LLNC without the addition of a Fenton's reagent or the production of Fe-sludge.